ChemInform Abstract: Catalytic Transformation of Aldehydes with Nickel Complexes Through η2 Coordination and Oxidative Cyclization. Issue 35 (September 2015) - Hoshimoto, Yoichi; Ohashi, Masato; Ogoshi, Sensuke
Abstract Review: 85 refs.